The Relationship Between Knowledge Level And Free Sexual Behavior Among Grade X Adolescents In Vocational High School Development Of Ambarukmo Science 1 Yogyakarta 2024 - Kurnia Dewi, Rika; Merida, Yunri; Hadi, Selasih Putri Isnawati (Universitas Prima Indonesia, 2025)
Background: Free sex is an influence of western culture that is adopted by the community without first being screened. The causative factors are poor association, lack of parental attention which has an impact on reproductive health such as STDs. The importance of sex education will prevent promiscuous sex. The purpose of this study is to ascertain the connection between the degree of knowledge and promiscuous sex behavior in class X adolescents at SMK Pembangunan Ilmu Ambarukmo 1. Research Method: This type of research uses a cross-sectional strategy. The Fisher's Exact Test was used to analyse the data in both univariate and bivariate ways utilising a population and a sample of 58 adolescents using the total population technique and questionnaire as a data collection instrument. Results: The degree of expertise of adolescents with a good level of 49 respondents (84.5%), and a poor level of 9 respondents (15.5%) and never engaged in promiscuous sexual behavior (91.4%) and 5 respondents (8.6%) had committed promiscuous sexual behavior. The results of the Fisher's Exact Test found a p-value of 0.000<0.05. Conclusion: There is a relationship between the level of knowledge and promiscuous sex behavior in class X adolescents at SMK Pembangunan Ilmu Ambarukmo 1